2020
DOI: 10.1111/ijcp.13797
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TRUS and combined MRI‐targeted plus systematic prostate biopsy for the concordance between biopsy and radical prostatectomy pathology

Abstract: Aim To evaluate the accuracy in histologic grading of MRI/US image fusion biopsy by comparing conventional 12‐core TRUS‐Bx at radical prostatectomy specimens (RP). Methods Consecutive patients diagnosed prostate cancer (127 with combination of both targeted biopsy (TBx) plus systematic biopsies (SBx) and separate patient cohort of 330 conventional TRUS‐Bx without mpMRI) with a PSA level of <20 ng/mL prior to RP were included. The primary end point was the grade group concordance between biopsy and RP pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Within recent years, multiparametric magnetic-resonance imaging (MRI)-target prostate biopsy (TB) of suspicious lesions in MRI, in addition to a systematic 12-core biopsy (SB), has become frequently employed [7]. Multiple studies and meta-analyses investigated a higher concordance of biopsy GS in the combined effect of TB + SB compared to SB alone regarding final pathological GS [8][9][10][11][12][13][14]. However, in these studies an undeniable proportion of patients are affected by up-or downgrading after pathological results.…”
Section: Introductionmentioning
confidence: 99%
“…Within recent years, multiparametric magnetic-resonance imaging (MRI)-target prostate biopsy (TB) of suspicious lesions in MRI, in addition to a systematic 12-core biopsy (SB), has become frequently employed [7]. Multiple studies and meta-analyses investigated a higher concordance of biopsy GS in the combined effect of TB + SB compared to SB alone regarding final pathological GS [8][9][10][11][12][13][14]. However, in these studies an undeniable proportion of patients are affected by up-or downgrading after pathological results.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, studies have shown that hybrid PET/CT and PET/MRI targeting PSMA are more accurate in the diagnosis of metastatic and recurrent PCa ( 85 87 ). In addition, invasive biopsy of PCa has a significant false negative rate ( 88 ), and studies have shown that guided biopsy of PCa by PSMA PET/CT can significantly improve the DR ( 59 , 76 ). Therefore, PSMA PET/CT is of great value in the diagnosis of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the novel field of radiomics has recently been exploited in PCa [ 215 ] and is expected to increase the accuracy of interpretation and prediction of the stage and outcome. Noteworthy, invasive biopsy has a significant false-negative rate [ 82 ], which can be reduced by the guidance of imaging. The role of PET/CT, PET/MRI and radiomics needs to be clarified for the guided biopsy of the prostate gland.…”
Section: Discussionmentioning
confidence: 99%
“…Uprimny et al reported patient-based sensitivity of 91% compared to the TRUS-guided biopsy [ 81 ]. However, it is known that TRUS-guided biopsy per se is suboptimal for the detection of primary PCa [ 82 ]. Several other publications addressed this issue, and ultimately in a meta-analysis, von Eyben et al reported the pooled lesion-based sensitivity and specificity of 70% (95% CI: 53–83%) and 84% (95% CI: 24–99%) for the detection of primary tumor, respectively [ 83 ].…”
Section: Targeting Agentsmentioning
confidence: 99%